Management of spasticity with onabotulinumtoxinA: practical guidance based on the italian real-life post-stroke spasticity survey - Sandrini, Giorgio (Funct Neurol, 2018)
The present paper provides practical guidance on the management of adult spasticity with OnabotulinumtoxinA. Advisory Board members reviewed the available evidence and discussed their personal experiences in order to address the unmet needs in the management of spasticity with botulinum toxin type A identified by the recent Italian Real-Life Post-Stroke Spasticity Survey. Stroke patients should be referred to spasticity services that have adequate facilities and multidisciplinary teams with the necessary training, competence and expertise. The current literature shows a strong correlation between the development of post-stroke spasticity and the degree of central sensorimotor system destruction/disorganization. Use of tools such as the Post-stroke Checklist may help clinicians in the long-term follow-up of stroke patients. The maximum dose of onabotulinumtoxinA — according to the current literature this ranges from 300U to 400U for upper limb and from 500U to 600U for lower limb aggregate postures — should be re-considered. In addition, there is a need for future consensus (also based on pharmacoeconomic considerations) on consistent clinical care models for the management of patients with post-stroke spasticity.